2019
DOI: 10.1002/dc.24216
|View full text |Cite
|
Sign up to set email alerts
|

Malignant teratoma of the thyroid: A difficult diagnosis by fine‐needle aspiration

Abstract: Primary thyroid teratomas are rare, usually benign, and typically occur in children. We report the unusual occurrence of a malignant thyroid teratoma in a young man. Initial ultrasound and CT studies revealed an 8.5 heterogeneous mass involving the entire right thyroid lobe causing tracheal compression and deviation. Fine‐needle aspiration (FNA) revealed malignant cells with possible neuroendocrine features. Similar findings have been previously reported, with an occasional interpretation as possible medullary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…In line with a distinct clinicopathological and molecular entity, malignant teratomas lack isochromosome 12, a genetic hallmark in the majority of germ cell neoplasms [9,[13][14][15][16]. Rabinowits et al reported in 2017 for the first time the presence of a pathogenic DICER1 mutation (c.5438A > G; p.Gln1813Glu) in a case of malignant thyroid teratoma in a 59-year-old female [9].…”
Section: Discussionmentioning
confidence: 98%
“…In line with a distinct clinicopathological and molecular entity, malignant teratomas lack isochromosome 12, a genetic hallmark in the majority of germ cell neoplasms [9,[13][14][15][16]. Rabinowits et al reported in 2017 for the first time the presence of a pathogenic DICER1 mutation (c.5438A > G; p.Gln1813Glu) in a case of malignant thyroid teratoma in a 59-year-old female [9].…”
Section: Discussionmentioning
confidence: 98%
“…More specifically, the location of recurrence in these 11 patients was the thyroid bed (n=4), the central compartment lymph nodes (n=3), the lateral lymph nodes (n=2) and the mediastinum (n=2). The proportion of patients who needed reoperation after their first surgery due to recurrence, either in the thyroid bed or in regional lymph nodes was 22.7% (n=5 out of 22 cases) (1,2,4,14,16). Distant metastases occurred in 8 (29.6%) patients; 5 (62.5%) had bone metastases, 3 (37.5%) had lung metastases and 3 (37.5%) were diagnosed with metastases in paraaortic and clavicular lymph nodes (4,11,(18)(19)(20).…”
Section: Literature Reviewmentioning
confidence: 98%
“…A total of 15 studies (11 case reports and 4 case series) described outcomes for 27 patients who were diagnosed with PTT and underwent thyroidectomy and in some cases an additional neck dissection (1,2,4,8,9,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). One study was excluded from the present systematic review (6).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, 12p gain has been described in other malignancies, including malignant teratoma of the thyroid (considered as an extragonadal germ cell tumor) [9] but also in pancreatic carcinomas [10]. However, the amplified region in pancreatic carcinomas is located proximal to the amplified region in TGCT [10].…”
Section: Introductionmentioning
confidence: 99%